The impact of work accidents experience on causal attributions and worker behaviour - Bogas, S.; Silva, S.A.; Lima, M. L.; Meliá, J. (Safety Science, 2008)
It has recently been suggested that the experience of work accidents is an important variable to be considered as a predictor of workers’ perceptions (e.g. causal attributions) and behaviours. Departing from the literature, this study has two goals: (1) to analyse the relationship among work accident experience, causal attribution of accidents and workers’ behaviour; and (2) to test causal attributions as a mediating variable in the relationship between work accident experience and workers’ behaviour. To test the stability of the results, the same analyses have been performed in two Portuguese organizations, one in an industrial context and the other in an R&D context. In the industrial organization, the sample is composed of 559 employees and in the R&D organization the sample is composed of 335 employees. Results show that work accident experience is positively associated with external attributions and unsafe behaviours and negatively associated with internal attributions. Moreover, the results reveal a complete mediation of the causal attributions in the industrial organization, although in the R&D organization the mediation was only partial.